Cultural pedagogy of empowerment of peripheral, blacks and LGBTQIA+ subjects: an analysis of the rap video clip AmarElo (Research, Society and Development, 2021)
Mass media and music can be considered cultural pedagogies, which convey messages, help educate and shape identities, on a broader perspective of education. Thus, the objective of this research is to describe and analyze the music video for the song “AmarElo” by Brazilian rapper Emicida, its characters’ life stories, and Internet users’ comments as products of a Cultural Pedagogy. The theoretical and methodological framework is supported by Cultural Studies and among contributions from anti-racist and queer theories. The method of analysis was based on Discourse Analysis and Semiology. The corpus was built based of the music video, a video about it characters, and 12 Internet users’ about the music video. The results revealed that: the characters are black people, LGBTQIA +, and residents of outskirts of the city, with overcoming life stories; the music video addresses the daily difficulties of these people, and on the other hand, their accomplishment and empowerment through study, work, sports, and arts. Internet users identify with the music video’s message and have a critical stance towards racism, homophobia, the socio-economic system, and the conservative political system. The music video “AmarElo” is a Cultural Pedagogy of resistance, overcoming and empowerment of individuals living in the outskirts, black and LGBTQIA+ subjects.